O processo de mediação no contexto do regime de informação: a construção de um espaço virtual de comunicação na web para a CPAD/UFPB - Brasileiro, Fellipe Sá (2013)
Presents an intervention in the regime of information in the camp of archives Federal University of Paraíba (UFPB), with goal to promote dissemination of archival information produced by the Standing Committee of Document Evaluation (CPAD), on scope the Campus I institution's, by building of one virtual space communication in the web and of actions of information appropriate. Broaches the process of mediation information in organizations as a set of information actions established based on the relations between the subjects and the networks Socio-communicational primary and secondary formed in the context of information regime that, through the resources offered by the infrastructure of cyberspace, are grouped into a single information environment in a form dynamic and effective. These actions are developed during the stages of production, organization and dissemination of information on the web, to which are find on collaboration of nature multidisciplinary between Marketing and Information Architecture for the web, the essential conditions for achieving the goals according to the characteristics and information needs of users. Accordingly, we used the methodology of action research so that permits the opinions, needs and experiences of subjects involved in the process of document management of CPAD to be considered regarding the planning and implementation of information actions. We departed from the application of semi-structured interview to obtain subsidies for the production and organization of information available on the web, following to the record of users' opinion regarding the evaluation of the information architecture of the website and then, ending with dissemination of information available on the web (website) through direct marketing. We conclude that both the construction of the website institutional of CPAD, as regards to the content of information architecture, regarding its dissemination, met the expectations of the servers involved in document management, as well as assisted in the promotion of CPAD within the institution, that is, giving visibility to the Table of Temporality document (TTD), the archival information and, especially, management practices that comprise the life cycle of documents.